Pelatihan Digital Accounting guna Peningkatan Kinerja Keuangan UMKM: Digital Accounting Training to Improve the Financial Performance of MSMEs - Sari, Arista Fauzi Kartika; Hariri, Hariri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
This community service program aims to improve the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in the Bandulan sub-district of Malang city through digital accounting training. This training is designed to improve understanding of basic accounting concepts and the use of accounting software to facilitate the recording of financial transactions that previously used manual recording. The training activities were carried out online and offline and were attended by 10 MSME participants, either as owners or in the finance department. The implementation method used was lectures to convey basic accounting concepts for MSMEs and practice operating digital accounting applications. The results of monitoring and evaluation showed that the value of MSME partners was at least 75 points, which means that partners can absorb the knowledge that has been carried out by the service team well. The results of this service can improve financial performance and effective and efficient management decision-making.